2022
DOI: 10.1039/d1fo03448k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, quality attributes and antioxidant activity of stirred-type yogurt enriched with Melastoma dodecandrum Lour fruit powder

Abstract: This study for the first time used Melastoma dodecandrum Lour fruits powder (MDLP) as a novel functional ingredient for improving stirred-type yogurt (STY) quality. Physicochemical, polyphenols content, antioxidant activity, texture...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 47 publications
(97 reference statements)
0
35
0
Order By: Relevance
“…In recent years, natural functional ingredients have attracted the great attention of many food scientists to produce functional foods that can improve health and wellness circles (Rashwan et al 2020;Rashwan et al 2021). Many foods and their ingredients were characterized as functional due to their unique nutritional compositions, such as sorghum, brown rice, beluga black lentils, black beans, berries, apple, grape, jujube, pomegranate, nuts, carrot, beetroot, cauliflower, purple potato, turmeric, cinnamon, salmon, sardines, and others (D'Amelia et al 2022;Espitia-Hernández et al 2022;Fadhlizil Fasihi Mohd Aluwi et al 2022;Feng et al 2022;Rashwan et al 2020;Rashwan et al 2022;Rashwan et al 2021). For example, sorghum extract contained a large number of bioactive compounds such as anthocyanins 2.4 μg/g, flavonoids 13.6 mg/g, and soluble polyphenols 102.1 mg/g (Bradwell et al 2018).…”
Section: Natural Functional Ingredientsmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, natural functional ingredients have attracted the great attention of many food scientists to produce functional foods that can improve health and wellness circles (Rashwan et al 2020;Rashwan et al 2021). Many foods and their ingredients were characterized as functional due to their unique nutritional compositions, such as sorghum, brown rice, beluga black lentils, black beans, berries, apple, grape, jujube, pomegranate, nuts, carrot, beetroot, cauliflower, purple potato, turmeric, cinnamon, salmon, sardines, and others (D'Amelia et al 2022;Espitia-Hernández et al 2022;Fadhlizil Fasihi Mohd Aluwi et al 2022;Feng et al 2022;Rashwan et al 2020;Rashwan et al 2022;Rashwan et al 2021). For example, sorghum extract contained a large number of bioactive compounds such as anthocyanins 2.4 μg/g, flavonoids 13.6 mg/g, and soluble polyphenols 102.1 mg/g (Bradwell et al 2018).…”
Section: Natural Functional Ingredientsmentioning
confidence: 99%
“…Consumers are now more informed about food and ingredients, especially functional foods, which have drawn much interest for their advantages in preventing several health problems, boosting several physiochemical functions, and providing high nutritional value. Therefore, several recent studies showed increased demand for these beneficial natural products (Crini et al 2020;Huang et al 2022;Qasim et al 2021;Rashwan et al 2022;Rashwan et al 2021;Suwannasang et al 2022;Tang et al 2022). Yogurt with functional ingredients is a type of functional food product that has been widely recognized and accepted by consumers; where health-conscious consumers have long considered yogurt to be a health-promoting product that could aid in digestion (Acevedo-Fani et al 2021;Liu et al 2022;Mada et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations